INTEGRATING THINK PAIR SHARE AND THREE STEP INTERVIEW TO ENHANCE STUDENTS’ SPEAKING ACHIEVEMENT - Dian Anggoro Pramesti Eba Utami; Ari Nurweni; Feni Munifatullah (Universitas PGRI Sumatera Barat, 2025)
This study aims to examine the improvement of students’ speaking achievement and their perceptions toward the implementation of integrated Think–Pair–Share (TPS) and Three-Step Interview (TSI). The research employed a one-group pretest–posttest design involving 30 ninth-grade students at SMPN 4 Metro. Instruments included a speaking test (pretest and posttest) and a perception questionnaire. Data were analyzed using a paired sample t-test and descriptive analysis. The results showed a significant improvement in students’ speaking scores from a pretest mean of 84.80 to a posttest mean of 89.40 (p < 0.05). Furthermore, students’ perceptions toward the TPS–TSI were positive with overall mean = 3.86, with the Target and Situation dimensions receiving the highest means, 3.94. These findings suggest that the integration of TPS–TSI not only enhances speaking skills but also fosters a supportive learning environment aligned with students’ future goals.